Resilience deficit index for quantification of resilience - Rohit Ranjan Singh; Michel Bruneau; Andreas Stavridis; Kallol Sett (Resilient Cities and Structures, 2022)
After a brief overview of how the dimensionless resilience index has been calculated in the past for buildings, and some of the shortcomings of that approach, the use of a resilience deficit index is advocated to overcome some of these shortcomings. An example is provided and the pros and cons of each approach are discussed, with broad recommendations applicable to the quantification of building resilience.